"Al wat kind is": iconic images of children in apartheid-era South African poetry. Issue 2 (4th May 2017) - Lewis, Simon Keith
ABSTRACT: Photographs of children have frequently proved to be the most iconic and emotive images to come out of conflict zones. Children have been used in similarly powerful ways in poetry too. This paper analyzes poetic representations of children and childhood by apartheid-era South African poets, including Lerato Kumalo, Chris van Wyk, and Ingrid de Kok. It pays particular attention to Ingrid Jonker's "The Child Who Was Shot Dead by Soldiers in Nyanga" and that poem's iconic after-life as manifested in Nelson Mandela's reading of the poem at the opening of the first democratically elected parliament in May 1994 and in the central role the poem plays in two film versions of Jonker's life, the feature film Black Butterflies, and the documentary A Mere Grain of Nothing My Death. The essay suggests that the status of children may make the best measure of progress towards Jonker's prophetic image of freedom.